Laparoscopic Ventral Rectopexy for Rectoanal Intussusception. Issue 4 (April 2015) - Tsunoda, Akira; Ohta, Tomoyuki; Kiyasu, Yoshiyuki; Kusanagi, Hiroshi
<x xml:space="preserve">Abstract</x> BACKGROUND: Laparoscopic ventral rectopexy can relieve symptoms of obstructed defecation and fecal incontinence in patients with rectoanal intussusception. However, pelvic floor imaging after surgery has not been reported. OBJECTIVE: This study was designed to assess the outcome of patients who underwent laparoscopic ventral rectopexy for rectoanal intussusception, with special reference to the postoperative findings on evacuation proctography. DESIGN: This study was a retrospective analysis of prospectively collected data. SETTING: The study was conducted from 2012 to 2013 at the Department of Surgery, Kameda Medical Center, Japan. PATIENTS: We included 26 patients with symptomatic rectoanal intussusception. INTERVENTION: Laparoscopic ventral rectopexy was performed. MAIN OUTCOME MEASURE: Evacuation proctography was performed before and 6 months after the procedure. Defecatory function was evaluated using the Constipation Scoring System and Fecal Incontinence Severity Index. RESULTS: Of 26 patients with rectoanal intussusception preoperatively, 22 had symptoms of obstructed defecation and 21 complained of fecal incontinence. Postoperatively, rectoanal intussusception was eliminated in all patients, though 8 developed recto rectal intussusception. There was an overall reduction in both grade 2 rectocele size (median preop 26 mm vs. postop 11 mm; p < 0.0001) and pelvic floor descent (median preop 26 mm vs. postop 20 mm; p < 0.0001). 6 months after surgery, a reduction of at least 50% was observed in the Constipation Scoring System score for 9 patients (41%) with obstructive defecation and in the Fecal Incontinence Severity Index score for 14 incontinent patients (67%). LIMITATIONS: This was a preliminary study with a small sample size, no control group, and short follow-up time. CONCLUSION: Evacuation proctography showed anatomical correction in patients with rectoanal intussusception who underwent laparoscopic ventral rectopexy. However, the data also indicate that such correction does not necessarily result in meaningful symptomatic relief.